Long COVID management: a mini review of current recommendations and underutilized modalities - Dietz, Tiffany K.; Brondstater, Kirsten N. (Frontiers in Medicine, 2024)
Long COVID is a condition that develops in a subset of patients after COVID-19 infection comprising of symptoms of varying severity encompassing multiple organ systems. Currently, long COVID is without consensus on a formal definition, identifiable biomarkers, and validated treatment. Long COVID is expected to be a long-term chronic condition for a subset of patients and is associated with suffering and incapacity. There is an urgent need for clear management guidelines for the primary care provider, who is essential in bridging the gap with more specialized care to improve quality of life and functionality in their patients living with long COVID. The purpose of this mini review is to provide primary care providers with the latest highlights from existing literature regarding the most common long COVID symptoms and current management recommendations. This review also highlights the underutilized interventions of stellate ganglion blocks and low-dose naltrexone, both with well-established safety profiles demonstrated to improve quality of life and functionality for patients suffering with some symptoms of long COVID, and encourages prompt referral to interventional pain management.